Evictionism, Pro-Life and Pro-Choice: A Response - Wojda, Paul (Roczniki Filozoficzne, 2025)
This short essay is a response to Walter Block’s “evictionist” alternative to the “pro-life” and “pro-choice” arguments over abortion. It addresses Block’s use of metaphors in the ongoing debate surrounding reproductive freedom and abortion in contemporary liberal democracies. It focuses specifically on Block’s libertarian framing of the pregnant woman as a “landlord” and the fetus as an “intruder” or “squatter”. The essay argues that these images are problematic and unlikely to help advance debate on reproductive liberty, abortion in particular, beyond its current impasse.